Theoretical concepts and practical implementation in enhancement of capacities for science-technology policy making - Hoa, Nguyen Viet (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Enhancement of capacities for science and technology (S&T) policy-making is the necessary requirements of many nations, particularly in context of the world’s economic crisis and tough competition between nations and regions. This paper deals with some basic aspects: theoretical concepts of capacities for S&T policy-making, objects for the enhancement of capacities for S&T policy making at macro and micro levels, and criteria of enhancement of capacities for S&T policy making. Code: 14091702